The category cultural routes and its meaning in the theoretical evolution of the concept cultural heritage - Martorell Carreño, Alberto (2018)
The inclusion of the category cultural heritage within the conceptual framework of the cultural heritage implies a deep change that could even be considered the arising of a new paradigm, despite of the fact that it follows a tendency previously marked by other inclusions (i.e. cultural landscape and serial heritage). Huge projects such as the Qhapaq Ñan and the Silk Road and others promoted by UNESCO are a demonstration of this statement. They imply a geographic scope and diversity that would even not be in the previous imagination. In this article, we follow the most important steps in this inclusive process which is arising the academic and cultural interest for the last years. There are, nevertheless, some conceptual gaps and vagueness which we analyze in this article. We make evident the necessity to generate an evaluation process of the progress made until now in this issue and to strengthen some values that the concept cultural routes itself makes evident.